Quantitative FLAIR analysis indicates predominant affection of the amygdala in antibody‐associated limbic encephalitis. Issue 9 (24th July 2013) - Wagner, Jan; Schoene‐Bake, Jan‐Christoph; Malter, Michael P.; Urbach, Horst; Huppertz, Hans‐Jürgen; Elger, Christian E.; Weber, Bernd
Summary Purpose Limbic encephalitis is an autoimmune‐mediated disease leading to temporal lobe epilepsy, mnestic deficits, and affective disturbances. Magnetic resonance imaging (MRI) usually shows signal and volume changes of the temporomesial structures. However, these abnormalities may be subtle, thereby hampering the diagnosis by conventional visual assessment. In the present study we evaluated the diagnostic value of a fully automated MRI postprocessing technique in limbic encephalitis and hippocampal sclerosis. Methods The MRI postprocessing was based largely on a recently described method allowing for an observer‐independent quantification of the fluid‐attenuated inversion recovery (FLAIR) signal intensities of amygdala and hippocampus. A 95% confidence region was calculated from the FLAIR intensities of 100 healthy controls. We applied this analysis to the MRI data of 39 patients with antibody‐associated limbic encephalitis and 63 patients with hippocampal sclerosis. Moreover, the results were compared to those of visual assessment by an experienced neuroradiologist. Key Findings The method detected limbic encephalitis and hippocampal sclerosis with a high sensitivity of 85% and 95%, respectively. The detection rate of the automated approach in limbic encephalitis was significantly superior to visual analysis (85% vs. 51%; p = 0.001), whereas no statistically significant difference for the detection rate in hippocampal sclerosis was found. Patients with limbic encephalitis had significantly higher absolute intensity values of the amygdala and a significantly higher percentage fell outside of the amygdalar confidence region compared to those with hippocampal sclerosis (79% vs. 27%; p < 0.001), whereas we found opposite results in the hippocampal analysis (38% vs. 95%; p < 0.001). Significance The FLAIR analysis applied in this study is a powerful tool to quantify signal changes of the amygdala and hippocampus in limbic encephalitis and hippocampal sclerosis. It significantly increases the diagnostic sensitivity in limbic encephalitis in comparison to conventional visual analysis. Furthermore, the method provides an interesting insight into the distinct properties of these two disease entities on MRI, indicating a predominant affection of the amygdala in limbic encephalitis, whereas the affection of the hippocampus is far less pronounced when compared to hippocampal sclerosis.